2010
DOI: 10.1038/cddis.2010.53
|View full text |Cite
|
Sign up to set email alerts
|

GX15-070 (obatoclax) overcomes glucocorticoid resistance in acute lymphoblastic leukemia through induction of apoptosis and autophagy

Abstract: Glucocorticoids (GCs) are common components of many chemotherapeutic regimens for lymphoid malignancies including acute lymphoblastic leukemia (ALL). The BCL-2 family has an essential role in regulating GC-induced cell death. Here we show that downregulation of antiapoptotic BCL-2 family proteins, especially MCL-1, enhances GC-induced cell death. Thus we target MCL-1 by using GX15-070 (obatoclax) in ALL cells. Treatment with GX15-070 in both dexamethasone (Dex)-sensitive and -resistant ALL cells shows effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 38 publications
6
84
0
Order By: Relevance
“…Stimulates obatoclax-induced apoptosis [131] Triggers caspase-3 activation Casp-3, -8, -9 (Beclin-1-C) Enhances IL-3 withdrawal-induced cell death [135] Targets mitochondria Induces Omi and cyt c release…”
Section: Beclin-1 Uncleavedmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulates obatoclax-induced apoptosis [131] Triggers caspase-3 activation Casp-3, -8, -9 (Beclin-1-C) Enhances IL-3 withdrawal-induced cell death [135] Targets mitochondria Induces Omi and cyt c release…”
Section: Beclin-1 Uncleavedmentioning
confidence: 99%
“…Furthermore, several Atg proteins were shown to trigger cell death and to engage the apoptotic pathway (Table 1). Atg5 was shown to directly bind Fas-associated protein with death domain (FADD), thereby triggering IFN-γ-induced cell death [129]; Atg7 mediates lysosome dysfunctioninduced apoptosis in neural cells [130]; and Beclin-1 stimulates apoptosis in response to the Bcl-2 inhibitor, obatoclax [131]. Moreover, a recent study uncovered the existence of an Atg12-Atg3 conjugation, which sensitizes cells to death downstream of mitochondrial pathways Table 1 List of Atg proteins exerting a pro-apoptotic function…”
Section: Apoptotic Cell Deathmentioning
confidence: 99%
“…Accordingly, an increasing number of reports suggest that there is indeed a complex interplay between autophagy and apoptosis, evidenced by the extensive molecular cross-talk between autophagy-related and apoptosis-related proteins. In this regard, several ATG proteins have been reported to engage the apoptotic pathway (61)(62)(63), whereas depletion of key autophagy regulators or pharmacological interference with autophagy has been shown to mitigate apoptosis (64). Conversely, several apoptotic proteins have been shown to regulate the autophagy process.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that increased Mcl-1 expression is associated with GC resistance (Holleman et al, 2004;Stam et al, 2010) and it has been demonstrated that Obatoclax treatment can rewww.intechopen.com sensitizes GC-resistant ALL cells (Bonapace et al, 2010). Other results suggest that Obatoclax could be useful as a therapeutic agent against ALL and that the activity and/or the expression of antiapoptotic proteins could be used as a biomarker to determine the appropriate treatment strategy for ALL patients (Heidari et al, 2010). In particular, Bonapace et al have shown that Obatoclax can overcome the resistance to GC through rapid activation of autophagy-dependent necroptosis, which was able to bypass the apoptotic block in the mitochondrion.…”
Section: Apoptosis Modulatorsmentioning
confidence: 99%